Retrospective evaluation of functional results and cost analysis of two different anesthesia methods in carpal tunnel syndrome surgery - Aykaç, Bilal (The European Research Journal, 2024)
Objective: The provision of health services at a satisfactory level and low cost is the main objective of all health systems. For this purpose, we evaluated carpal tunnel surgery performed under local anesthesia in the local procedure room and under a laryngeal mask in the operating room in terms of cost analysis. In this way, we aimed to reveal the controllability of health service expenditures and inadequacies in costing. Methods: A total of 119 patients who underwent local anesthesia (LA) in the local procedure room (Group I) and 45 patients who underwent laryngeal mask anesthesia (LMA) in the operating room (Group II) were retrospectively evaluated. In the calculation of cost analysis, since there were no hospitalization procedures in Group I cases, total costs were calculated only in minutes, multiplied by a coefficient of 7. In Group II cases, total costs were calculated by multiplying total procedure times in minutes by a coefficient of 12 and adding 50 units of hospitalization cost. Results: Postoperative Quick Disabilities of the Arm, Shoulder, and Hand score is statistically similar in both groups (P=0.714). The operation duration has an average value of 15.39±2.37 in the group of patients who received local anesthesia and 29.71±4.78 in the group treated in the operating room (P<0.001). It has been found that the intervention performed in the operating room is 2.2 times more costly than the local intervention. Conclusion: Our study is extremely valuable in terms of demonstrating that health service expenditures can be controlled in appropriately selected patients.